Relationship between early clinical characteristics and long term disability outcomes: 16 year cohort study (follow-up) of the pivotal interferon β-1b trial in multiple sclerosis. Issue 3 (21st December 2011) - Goodin, Douglas S; Traboulsee, Anthony; Knappertz, Volker; Reder, Anthony T; Li, David; Langdon, Dawn; Wolf, Christian; Beckmann, Karola; Konieczny, Andreas; Ebers, George C; ,
Abstract : Background: Evaluating the long term benefit of therapy in multiple sclerosis (MS) is challenging. Although randomised controlled trials (RCTs) demonstrate therapeutic benefits on short term outcomes, the relationship between these outcomes and late disability is not established. Methods: In a patient cohort from the pivotal interferon β-1b trial, the value of clinical and MRI measures were analysed, both at baseline and during the RCT, for predicting long term physical and cognitive outcome. Results: Baseline disability correlated with both physical (R 2 =0.22; p<0.0001) and cognitive (R 2 =0.12; p<0.0001) outcome after 16 years. Accrual of disability during the RCT (R 2 =0.12; p<0.0001) and annualised relapse rates during the trial correlated with physical outcome (R 2 =0.12; p<0.0001) but not with cognition. In contrast, baseline MRI measures of atrophy and lesion burden correlated with cognitive (R 2 =0.21; p<0.0001), but not with physical, outcome. Accumulation of plaque burden measured by MRI did not correlate with late physical disability or with cognitive outcome. Multivariate regression analysis using stepwise elimination demonstrated that baseline variables contributed independently to predicting long term outcomes while trial outcome variables contributed little. Overall, and considerably dependent on baseline measures, the models developed by this method accounted for approximately half of the variance in long term cognitive and disability outcome. Conclusions: Although on-trial change in some short term clinical measures correlated with long term physical and disability outcomes, the proportion of the variance explained by single commonly employed on-study variables was often small or undetectable. Better correlations were observed for several baseline measures, suggesting that long term outcome in MS may be largely determined early in the disease course. Trial registration number: http://Clinical Trials.gov, study registration NCT00206635 .